Pengaruh Zakat terhadap Rasio Net Profit Margin (NPM) pada PT. Bank Syariah Mandiri Tbk. - Pipi Sumanni Manullang; Nofinawati Nofinawati; Jumi Atika (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Abstract There is an increase or decrease in zakat followed by the ratio of Net Profit Margin (NPM), which is not in accordance with the theory. The purpose of this study was to determine the effect of zakat on the ratio of Net Profit Margin (NPM) at PT. Bank Syariah Mandiri Tbk. This research is a quantitative research with a descriptive approach. The data source used is secondary data. The analytical tools used are descriptive statistics, normality test, linearity test, simple linear regression test, coefficient of determination, and partial regression coefficient test (t test). The results of the study with the equation NPM = 5,299 - 0.135 X + 0.066 and the R Square data is 0.131 or 13.1%, this means that the zakat variable explains that the Net Profit Margin ratio (NPM) in PT. Bank Syariah Mandiri Tbk. influenced by 13.1%, while the remaining 86.9% is influenced by other variables not included in this research model. For the t test results, there is a significant influence between zakat and the ratio of Net Profit Margin (NPM).Keywords: Net Profit Margin Ratio (NPM), and Zakat